EVALUASI MANAGEMEN LAKTASI IBU MUDA DI POSYANDU RAMBUTAN 5 - Anggraeni*, Zuhrotul Eka Yulis (The Indonesian Journal of Health Science, 2016)
Breastfeding is a nature if every woman who has a child, and it?s a complex condition since it need an optimal preparation so that a mother could give optimal breastmilk for her baby. Lactation management programme for pregnant mother is based on the consecquences of growth and developmental proccess of the baby from the womb untill she born and at golden period of her early life. This research are conduct to find out the lactation management programme of young mother through pregnancy and after the baby has born. It?s a descriptional research with cross sectional approach and the data used are restrospective data. The respondent are all of young mother in Posyandu Rambutan 5. The result show that the evaluation of lactation management programme is in good enough category.  Mother?s knowledge and application of lactation management in posyandu rambutan 5 should be improved.Keyword : management, lactation, young mother